2008
DOI: 10.1002/masy.200851109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Nucleation in Pressure Sensitive Adhesive Properties: Miniemulsion versus Emulsion Polymerization

Abstract: Miniemulsion polymerization is a promising approach to produce and tailor pressure sensitive adhesives (PSAs). In this paper, a systematic comparison of the adhesive properties of latexes produced by miniemulsion and conventional emulsion polymerization is presented. Specifically, the influence of the total surfactant concentration, chain transfer agent concentration and chemical composition on the final adhesive properties of the polymer 2‐ethyl hexyl acrylate/methyl methacrylate/acrylic acid was discerned us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Fonseca et al. [ 18,60 ] showed that PSAs from MEP and CEP have different microstructure, and therefore different viscoelastic properties. They found that MEP resulted in lower molecular weight (MW) polymer due to the lower polymer concentration, on average, in the polymerizing particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fonseca et al. [ 18,60 ] showed that PSAs from MEP and CEP have different microstructure, and therefore different viscoelastic properties. They found that MEP resulted in lower molecular weight (MW) polymer due to the lower polymer concentration, on average, in the polymerizing particles.…”
Section: Resultsmentioning
confidence: 99%
“…They found that MEP resulted in lower molecular weight (MW) polymer due to the lower polymer concentration, on average, in the polymerizing particles. [ 60 ] PSAs produced via MEP showed superior tack and peel strength, which was attributed to their higher entanglement density, i.e., the ratio of polymer molecular weight divided by the entanglement molecular weight ( M w / M e ). [ 18 ] Our results similarly showed higher tack and peel strength for PSAs synthesized via MEP compared to CEP at 0 wt% CNC loading (Figure 5A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Some investigations have been carried out to study the influence of the CTA and the polymer molecular characteristics on the adhesion performance of the resulting PSAs . For example, Ravindra et al .…”
Section: Introductionmentioning
confidence: 99%
“…In situ synthesis and properties of hydrogenated rosin/polyacrylate composite miniemulsions-based pressure sensitive adhesives 1…”
Section: In Situ Synthesis and Properties Of Hydrogenated Rosin/polyamentioning
confidence: 99%
“…[1][2][3][4] However, some technical problems still need to be solved with further effort, for example, the usage of the surfactant and the monomer containing carboxyl groups lead to the latex films' low resistance to water, the adhesion properties of polyacrylate emulsions especially for the nonpolar materials such as polyolefin are relatively poor. [5][6][7] Therefore, the application of the polyacrylate emulsions is restrained at a certain degree.…”
Section: Introductionmentioning
confidence: 99%